Crime propensity and lifestyle risk: the interplay of personal morality and self-control ability in determining the signiﬁcance of criminogenic exposure - Hirtenlehner, Helmut (European journal of criminology, 2025)
According to Situational Action Theory, acts of crime are the result of a propensity—exposure interaction, with greater effects of criminogenic exposure for people of higher crime propensity—the latter determined by personal morality and the ability to exercise self-control. The present study delves into this interplay using individual-level survey data from adolescents in Slovenia. It goes beyond extant research by explicitly testing the three-way interaction of personal morality, self-control ability and a criminogenic lifestyle. Employing a respondent's lifestyle risk as proxy measure of the extent of exposure to crime-conducive settings, supportive results are obtained. An individual's lifestyle risk fosters criminal activity particularly among those with higher crime propensity. There is also evidence of a complex three-way interaction according to which self-control ability protects against detrimental lifestyle risk effects mainly among adolescents exhibiting weak morality. This suggests that personal morality and the capacity for self-control jointly and interdependently condition the significance of criminogenic exposure.